Etanercept, improved dosage schedules and combinations in the treatment of psoriasis: an update - Siegfried Segaert (Dove Medical Press, 2009)
Siegfried SegaertDepartment of Dermatology, University Hospital Leuven, BelgiumAbstract: Etanercept, a subcutaneously administered fully human soluble tumor necrosis factor (TNF) receptor, was initially approved for the treatment of psoriasis at a dose of 25 mg twice weekly in repeated 24-week cycles with the possibility to double the dose in the first 12 weeks of the first cycle. During intermittent treatment, patients retain their ability to respond to etanercept. Recently, a new dosing schedule of etanercept 50 mg once weekly was approved, based on a study in which PASI-75 (75% improvement of Psoriasis Area and Severity Index) was achieved by 37% and 71% of patients at week 12 and 24. Another study demonstrated a PASI-75 of 57% and 69% in pediatric psoriasis patients receiving etanercept 0.8 mg/kg (up to 50 mg) once weekly for 12 and 24 weeks respectively, resulting in European approval from age 8. Based on recent clinical trials, the antipsoriatic effect of etanercept can be markedly increased in combination with acitretin, methotrexate or UVB. The combination with acitretin appears attractive because of its non-immunosuppressive and chemopreventive properties. Etanercept–methotrexate combination therapy is well established in rheumatologic patients. From a long-term perspective, the combination of TNF-inhibitors with phototherapy (photocarcinogenesis) or cyclosporine (carcinogenesis, infections) warrants great caution however. Finally, combination with topical calcipotriol–betamethasone ointment may increase the speed of response to TNF-inhibitors in the first 4 weeks of treatment.Keywords: etanercept, psoriasis, dosing schedules, combination therapy